Minimum Spanning Tree for the Implementation of Kruskal’s Algorithm - Paryati, Paryati; Yazid, Ahmad Subhan (IJID (International Journal on Informatics for Development), 2014)
Kruskal?s algorithm is an algorithm used to find a minimum spanning tree in graph connectivity which gives an option to keep processing the edge limit with the least weight. In a Kruskal?s algorithm, the weight sorting of edge value will ease the finding of the shortest path. This algorithm has independent nature which will ease and enhance the path track making.